CREATION, PHYSICAL AND CHEMICAL PROPERTIES OF ALKIL-2-((5-PHENETHYL-4-R-1,2,4- TRIAZOLE-3-YL)THIO)ACET(PROPAN,BENZ)IMIDATES - TATYANA, IGNATOVA; ANDRIY, KAPLAUSHENKO; NATALIYA, NAGORNA; ANTONINA, AVRAMENKO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this research was to synthesize and evaluate physical-chemical properties of 5-pheneyhyl-4-R-3-thio-1,2,4-triazole and to establish identity and structure of the synthesized compounds, namely alkil-2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio)acet(propan,benz)imidates. Methods: As starting materials for synthesis of alkil-2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio)acet(propan,benz)imidates, the corresponding 2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio)aceto(propane,benzo)nitrile have been used. Synthesis has been set in the absolute alcohol medium (propanol or butanol alcohol) with chloroform, using the saturation with dry hydrogen chloride. Results: In this study, we have developed nine new compounds have been received as a result of synthetic transformations, the structure of synthesized compounds has been confirmed by modern complex of physical-chemical methods of analysis (1H NMR-spectroscopy, elemental analysis), and their individuality has been conducted on gas-liquid chromatograph Agilent 1260 Infinity HPLC equipped with a mass spectrometer Agilent 6120. Conclusion: As a result of the work, it was synthesized the new compounds of the series of alkil-2-((5-phenethyl-4-R-1,2,4-triazole-3-yl)thio) acet(propan,benz)imidates and was characterized by elemental analysis and proton nuclear magnetic resonance spectroscopic analysis.